Whether profitability and investment factors have additional explanatory power comparing with Fama-French Three-Factor Model: Empirical evidence on Chinese A-share stock market - Wenting Jiao; Jean-Jacques Lilti (China Finance and Economic Review, 2017)
Background: Fama and French propose a five-factor model that contains the market factor and factors related to size, book-to-market equity ratio, profitability, and investment, which outperforms the Fama-French Three-Factor Model in their paper in 2014. This study investigates the performance of Fama-French Five-Factor Model and compare with that of Fama-French Three-Factor Model on Chinese A-share stock market. Methods: Portfolios are constructed following Fama and French method. The OLS is applied to running time-series regressions; the t-statistics of regression coefficients are corrected for heteroscedasticity and autocorrelation using the Newey-West estimator with five lags. Results: The empirical results show that Fama-French Five-Factor Model explanatory power has differences among different sets of portfolios. In comparison with Fama-French Three-Factor Model, the presence of profitability and investment factors seem not to capture more variations of expected stock returns than the three-factor model except for six value-weighted portfolios formed on size and operating profitability. Conclusions: Profitability and investment factors do not have much additional explanatory power, and Fama-French Five-Factor Model does not have significant improvement in explaining average excess stock returns comparing with the original three-factor model on Chinese A-share stock market, which is inconsistent with the findings on US stock market.
Keywords: 330; Profitability factor; Investment factor; Fama-French Five-Factor Model; Chinese A-share stock market